Watershed management against watershed degradation in the Caribbean. - GUMBS, F.A. (1996)
Describes the tillage and soil conservation methods that are used, or considered suitable for use on sloping land in the Caribbean. Groups the soil conservation methods into agronomic or cultural practices and engineering practices.